A dynamic cutting force model for transverse orthogonal cutting of unidirectional carbon/carbon composites considering fiber distribution. (1st November 2020) - Shan, Chenwei; Zhang, Menghua; Yang, Yang; Zhang, Shengnan; Luo, Ming
Abstract: Many unwanted defects such as burr and delamination can be induced due to the high cutting forces in the machining process of carbon/carbon (C/C) composites due to their brittle property. In this regard, it is necessary to predict the cutting force accurately in the machining of C/C composites. In this paper, a prediction model of dynamic cutting force in time domain is proposed for transverse orthogonal cutting of unidirectional C/C (UD-C/C) composites based on the energy method considering the random distribution of fibers and voids. Firstly, a microscopic representative volume element (MRVE) consisting of a single carbon fiber and its surrounding carbon matrix is introduced into this model, and its size varies with the distribution of fibers and voids. Then, the cutting force model of a MRVE is established considering the fiber orientation angle. Second, the representative volume element (RVE) of transverse cross section of UD-C/C composites is simulated mathematically with the random distribution of fibers and voids. The instantaneous resultant cutting force model in time domain is developed by integrating the cutting force of the in-cut MRVEs. The comparison of the predicted and experimental cutting forces shows a good agreement.